Evaluation of three carbon sources for the biological treatment of acid mine drainage through process modelling - Gopal, Hemant (Department of Chemical Engineering, 2023)
South Africa is considered to be a semi arid to arid country (Harrison, 2004), hence its water resources are of great importance. In South Africa, the principal contributors to extensive sulphate pollution of ground water are the industries mining coal and metalbearing sulphidic minerals, which gives rise to the production of acid mine drainage (AMO). AMO is generated from both active and abandoned mining areas. The metal sulphides in the metal tailings are oxidised to produce large amounts of dissolved metals, sulphates and acids. These metals and acids constitute acid mine drainage. This natural process results from the exposure of ores to atmospheric conditions coupled with bacterial activity (Tsukamoto and Miller, 1999). Pollution by AMO can have a devastating effect on terrestrial and aquatic ecosystems. It is a long-term environmental problem since the oxidation of the metal sulphides can continue indefinitely after the closure of the mine {Tsukamoto and Miller, 1999). The traditional method of treating AMO is by neutralisation of the acid through the addition of lime (Santos et al., 2004). More recently, biological treatment of AMO has become attractive. However, a concern with this method is the requirement and availability of cost effective and efficient sources of carbon and electron donors. This thesis aims to evaluate three different substrates as sources of carbon and electron donor capacity (ethanol, molasses and primary sewage sludge) in terms of their availability and their impact on both final water quality and process economics. It seeks to determine the extent to which the carbon substrate is the limiting factor in terms of process economics. Further to the economic analysis, analysis of substrate requirements as a function of availability as well as impact of substrate used on process complexity and water quality is reviewed. These goals are approached through use of a process model. Data for the development of the model and its calibration has been taken from the literature. After an extensive review of the literature, a model of the anaerobic digestion process has been compiled using Excel, with the reactor being simulated using MATLAB. The program for the reactor is based on the simulation developed by Knobel (1999) in OCTA VE. The reactor was simulated as a CSTR that was well mixed and had no biomass retention. The statistical method used to verify the fit of the model to the data was the Chisquare statistic. This is a good method of comparing the model data with literature data as it showed the degree of deviation of the model from the literature values. The values obtained from this calculation were then compared to the critical value of i' at the 90% confidence level. The model was verified against four sets of anaerobic digestion data from literature with the carbon source being of various complexities. The results of the mass balance showed that AMD site 3 required the highest concentration of carbon substrate owing to the highest concentration of sulphate entering the system. AMD site 3 also had the highest production of H2S gas from both the anaerobic reactor as well as the mixer. As AMD site 3 treated the highest concentration of sulphate, it also produced the highest amounts of by-products. In the same respect, AMD site 1 treated the lowest concentration of sulphates and produced the least amount of by-products. The simulation was set up such that the final effluent sulphate concentration met the EPA standard of250 mg r1 and a sulphide level ofless than 10 mg rt. The only water parameter that needed analysis was the COD levels. The recommended COD level in the final effluent was 75 mg rt (DW AF, 1996 and Finn, 2004). Using the proposed flowsheet, only systems using ethanol as a carbon substrate approached this criterion. Both the molasses and primary sewage sludge systems failed to achieve this using the well mixed reactor system described by the model. For molasses or primary sewage sludge to meet the required COD levels, a reactor that could uncouple the hydraulic residence time and solids residence time and have high solids retention, would be required. The capital costing of the treatment plants was based on pricing obtained by Ball and Schroeder (2001) who had previously costed similar units. A factorial method was used for the cost scaling of the units. Inflation was also taken into account. The operating cost of the system was based on the methods presented in Sinnott (2000) and Turton et al. (1998). The economic results showed that using stainless steel was 16 times more expensive than using reinforced concrete as the material of construction. Hence, all further work was done on the basis of using reinforced concrete as the material of construction. Ethanol was found to be the most economically viable choice when the cost saving on the disposal of primary sewage sludge was not taken into account. Using a complex particulate carbon source such as primary sewage sludge as the carbon substrate proved to be the most expensive option of the three where no benefit of reduced disposal costs of this complex particulate was found. However, when the savings resulting from reduced disposal requirements of primary sewage sludge from wastewater treatment were included, primary sewage sludge proved to be the most economically viable option. This was an important finding as it showed that there was a high burden reduction on the wastewater treatment works and hence should be strongly recommended for use in the treatment of acid mine drainage. As a corollary to this, the ongoing development of reactor systems exploiting the uncoupling of hydraulic and sludge residence times and maximising sludge retention is of prime importance.